New prognostistic markers of nodular forms of goiter combined with autoimmune thyroiditis - Sheremet, M. I.; Sydorchuk, L. P.; Shidlovskyi, V. O.; Bedenyuk, A. D.; Pashkovska, N. V.; Leonova, M. O.; Chorna, O. O.; Stankova, N. I.; Rybak, O. V. (Journal of Education, Health and Sport, 2017)
Background: Based on the results of a histological study of removed TG tissue NGAIT was found in 10,4% of the patients [1, 2]. At the same time, we observe processes of both thyroid epithelium metaplasia and lymphoid tissue hyperplasia that, undoubtedly, can be considered as an optional precancerous condition [3-8]. The option when cytomorphological and immunocytochemical examinations are carried out sequentially, using the same smear of a puncture material is optimal for PCE [9]. Methods: We have carried out an immunohistochemical study by means of monoclonal antibodies against Fas, FasL, Bcl-2, P53 and Ki67 antigens using the thyroid gland puncture material. Results: The results showed the degree of proliferative activity in the thyroid tissue in NGAIT. We found a high proliferative activity of lymphoid tissue, moderate proliferative activity of thyroid epithelial cells in the area of lymphoid infiltration and a low one – beyond the latter. Conclusions: The pronounced expression of Fas and FasL on the thyroid epithelial cells in the area of lymphoid infiltration indirectly indicates that NGAIT causes the processes of thyroid epithelial cells apoptosis due to the immunity. Increasing the number of immunoreactive cells expressing Ki67 in the area of lymphoid infiltration and destruction of thyroid epithelial cells, are indicative of follicular epithelial regeneration as a compensatory-adaptive response of the organ. A pronounced Bsl-2 expression in lymphocytes prevents the cells from entering apoptosis and prolongs the cell survival time. There was a high expression of p53 protein in the nuclei of thyroid epithelial cells and follicular lamina, which can be explained by mutations in the gene p53, which allows the cells to find tolerance to apoptotic action of the immune system effectors. Abbreviations: NGAIT - nodular goiter combined with autoimmune thyroiditis, TG – thyroid gland, PCE – preoperative cytological examination.